Polymorphism in the growth hormone gene, weight in infancy, and adult bone mass. - Dennison, E; Syddall, H; Rodriguez, S; Voropanov, A; Day, I; Cooper, C (2004)
Epidemiological studies point to the importance of gene-environment interactions during early life as determinants of later osteoporosis and fracture. We examined associations between common single nucleotide polymorphisms in the human GH (GH1) gene and weight in infancy, adult bone mass and bone loss rates, and circulating GH profiles. Two hundred and five men and 132 women, aged 61-73 yr, in the Hertfordshire Cohort Study were included; bone mineral density was measured by dual energy x-ray absorptiometry over 4 yr. Twenty-four-hour circulating GH profiles were constructed in a subset of 71 men and women. Genomic DNA was examined for two single nucleotide polymorphisms in the GH gene (one in the promoter region and one in intron 4). Homozygotes at loci GH1 A5157G and T6331A displayed low baseline bone density and accelerated bone loss; there was also a significant (P = 0.04) interaction among weight at 1 yr, GH1 genotype, and bone loss rate. There was a graded association between alleles and circulating GH concentration among men. This study suggests that common diversity in the GH1 region predisposes to osteoporosis via effects on the level of GH expression. The interaction with infant weight suggests that early environment may influence the effect of GH1 genotype on bone loss.